2021
DOI: 10.1016/j.heliyon.2021.e06706
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of COVID-19 patients with diabetes mellitus in Kuwait

Abstract: Background COVID-19 has a highly variable clinical presentation, ranging from asymptomatic to severe respiratory symptoms and death. Diabetes seems to be one of the main comorbidities contributing to a worse COVID-19 outcome. Objective In here we analyze the clinical characteristics and outcomes of diabetic COVID-19 patients Kuwait. Methods In this single-center, retrospective study of 417 consecutive COVID-19 patients, we analyze and compare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…To date, more than 190 million people worldwide have been diagnosed with COVID-19, with an overall prevalence rate of at least 2% (1). Although, mortality rates are generally lower (2.2%), the presence of preexisting health conditions such as T2DM, hypertension, cardiovascular disease, and metabolic syndrome may contribute to increased case fatality rates up to 10% (2)(3)(4). A myriad of factors may contribute to increased susceptibility of T2DM patients for developing COVID-19 complications, including impaired innate/adaptive immunity, after the onset of a state of chronic, low-grade inflammation called metabolic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 190 million people worldwide have been diagnosed with COVID-19, with an overall prevalence rate of at least 2% (1). Although, mortality rates are generally lower (2.2%), the presence of preexisting health conditions such as T2DM, hypertension, cardiovascular disease, and metabolic syndrome may contribute to increased case fatality rates up to 10% (2)(3)(4). A myriad of factors may contribute to increased susceptibility of T2DM patients for developing COVID-19 complications, including impaired innate/adaptive immunity, after the onset of a state of chronic, low-grade inflammation called metabolic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study specifically in people with type 2 diabetes in Kuwait suggests that diabetes patients with COVID‐19 have poor clinical prognosis. 10 …”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of whether diabetes is a particular risk factor for poor COVID‐19 outcomes in the Middle East, since the severity and prevalence of type 2 diabetes is distinct in this area of the world. One recent study specifically in people with type 2 diabetes in Kuwait suggests that diabetes patients with COVID‐19 have poor clinical prognosis 10 …”
Section: Introductionmentioning
confidence: 99%
“…Oxygen saturation (SpO2 < 90%) is significantly decreased in these types of patients indicating that CRP levels are increased in severe lung injury patients [ 66 ]. Increased CRP were reported in 13 studies [ 37 , 38 , 40 , 43 , 47–49 , 51 , 54 , 61–64 ], where patients were separated into two groups: diabetic and non-diabetic. This result showed that increased CRP was highly associated with severe conditions of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%